2001
DOI: 10.1037/0021-9010.86.2.351
|View full text |Cite
|
Sign up to set email alerts
|

Achieving desired images while avoiding undesired images: Exploring the role of self-monitoring in impression management.

Abstract: A study was conducted to test the hypothesis that high self-monitors more effectively manage impressions than low self-monitors do. Students in work groups indicated the extent to which they used 5 impression-management tactics over the course of a semester-long project. At the project's conclusion, students provided their perceptions of the other members of their group. The relationship between impression management and image favorability was then examined across 339 student-student dyads. The results general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
400
2
15

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(430 citation statements)
references
References 43 publications
13
400
2
15
Order By: Relevance
“…Others 23 have found that those claiming a high degree of ability ('high self-monitors') can use impression management Impression management score Self-assessment -mean of assessors tactics more effectively than 'low self-monitors' . In particular, 'high self-monitors' appear to be more adept at using ingratiation and self-promotion to achieve favourable images among their colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Others 23 have found that those claiming a high degree of ability ('high self-monitors') can use impression management Impression management score Self-assessment -mean of assessors tactics more effectively than 'low self-monitors' . In particular, 'high self-monitors' appear to be more adept at using ingratiation and self-promotion to achieve favourable images among their colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…For those higher in perceived job mobility, rather than challenging their belief of having higher job mobility, managers may help them find effective ways to increase their social acceptance at work and to cope with their discomfort from being ostracised, such as by building their social and political skills (Ferris et al, 2007;Hogan & Shelton, 1998). Increasing their social awareness may help them engage impression management tactics to construct positive images, such as promoting themselves in a way to be perceived as being competent instead of conceited (Turnley & Bolino, 2001), and thus mitigate the levels of ostracism. Based on the role of organizational identification, managers or organizations can also seek to strengthen employees' organizational identification in other ways, such as building a shared organizational vision, showing organizational support to employees, and promoting communication and cooperation among employees (Scott, 1997).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…This measure should be less sensitive to social desirability biases (Turnley and Bolino 2001) than common measures that focus on risk propensity (Sitkin and Pablo 1992;Sitkin and Weingart 1995;White et al 2006), as project managers do not rate their own risk preference or risk-taking behavior, but instead describe their practical experience with project management. An alternative measure would have been to ask participants whether they consider their estimates to be more optimistic or pessimistic, but again we would face social desirability and self-perception biases: No experienced project manager could, for example, be expected to admit that she or he is repeatedly underestimating task-completion times or risk occurrence probabilities.…”
Section: Risk Awarenessmentioning
confidence: 99%